HOW TO ANSWER CHILDREN QUESTIONS - O. Brenifier (Russian State Vocational Pedagogical University, 2016)
The aim of the investigation is to disclose the possible philosophicalconversation with the child.Methods. The author uses general scientific research methods, including observation and interviews, philosophical analysis.Results and scientific novelty. The author reveals the essence of philosophical conversations with the child, calls the main reasons for the extinction of the children's curiosity, illustrating examples of incorrect behavior of adults to communicate with children. It is recommended how to be responsible for children's issues. The article discusses the main reasons for the extinction of the children's curiosity by illustrating examples of an erroneous behaviour of adults in dealing with children. It is shown that if the teacher does not find a systematic way to engage children in the essential discussion, the children most likely will not learn how to contemplate seriously. The author gives detailed guidance how to answer children's questions.Practical significance. The article may be of interest to parents, teachers, experts in the field of psychology of creativity, post-graduates and organizers of independent activity of students of higher education institutions.